World Englishes in English language teaching: Kachru's six fallacies and the TEIL paradigm - Matsuda, Aya (World Englishes, 2019)
In recent years, there has been increased interest among English language teaching (ELT) professionals in world Englishes (WE) studies. This article examines the influence of Braj Kachru's work and WE studies in general on ELT. After a brief historical overview of the disciplinary relationship between WE and ELT, it discusses the current place of WE in ELT and presents the framework of Teaching English as an International Language (TEIL), an innovative paradigm in ELT that heavily draws from WE. The article ends with insights into future, speculating how WE will continue to be resourceful to ELT.